Akad Mudharabah dan Implikasinya terhadap Stabilitas Produk Perbankan Syariah di Indonesia - Anas Lutfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The mudharabah contract is one of the main pillars in Islamic banking products that functions as a partnership-based financing model. However, the implementation of this contract often faces challenges related to financial stability, such as the risk of disproportionate profit sharing and potential moral hazards. This article aims to analyze the implications of mudharabah contracts on the stability of Islamic banking products in Indonesia. The research method uses a library research approach by examining classical and contemporary literature related to mudharabah contracts, Islamic banking regulations, and relevant case studies. The results of the study show that the stability of mudharabah-based products is greatly influenced by sharia compliance, contract transparency, and effective risk management. In conclusion, optimizing the implementation of mudharabah contracts requires strengthening regulations and education to banks and customers.